A comprehensive survey on nature‐inspired algorithms and their applications in edge computing: Challenges and future directions. (20th September 2021) - Adhikari, Mainak; Srirama, Satish Narayana; Amgoth, Tarachand
Abstract: Driven by the vision of real‐time applications and smart communication, recent years have witnessed a paradigm shift from centralized cloud computing toward distributed edge computing. The main features of edge computing are to drag the cloud services toward the network edge with dramatic reductions of latency while increasing the resource utilization of the network and computing devices. Being the natural extension of cloud computing, edge computing inherits a variety of research challenges and brings forth different new issues to solve. These challenges are dealing with solving complex optimization problems including scheduling and processing real‐time applications. Nature‐inspired meta‐heuristic (NIMH) algorithm is an overarching term in the field of an optimization problem that provides robust solutions to the NP‐complete problems, from computationally tractable approximate solutions to real‐time optimization strategies. Nowadays, different NIMH algorithms have been applied in the field of edge computing for solving various research challenges including resource placement and scheduling, communication, mobility, and edge controlling with higher efficiency. In this survey, we classify the existing NIMH into three categories based on their nature of works and included fuzzy logic and systems in the field of edge networks along with different research challenges. Further, we introduce different challenges and future directions to identify promising research works in edge computing.